2013
DOI: 10.1523/jneurosci.4601-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Amodal Processing in Human Prefrontal Cortex

Abstract: Information enters the cortex via modality-specific sensory regions, whereas actions are produced by modality-specific motor regions. Intervening central stages of information processing map sensation to behavior. Humans perform this central processing in a flexible, abstract manner such that sensory information in any modality can lead to response via any motor system. Cognitive theories account for such flexible behavior by positing amodal central information processing (e.g., "central executive," Baddeley a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 85 publications
1
28
0
Order By: Relevance
“…These methods may have been critical to resolving multiple distinct visual-biased and auditory-biased attention regions where prior studies found responses independent of sensory modality. Consistent with our findings, a recent multivariate analysis study indicated that posterior lateral frontal cortex contains information about sensory modality, but this study did not identify specific visual-biased and auditory-biased frontal cortical areas (Tamber-Rosenau et al, 2013). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These methods may have been critical to resolving multiple distinct visual-biased and auditory-biased attention regions where prior studies found responses independent of sensory modality. Consistent with our findings, a recent multivariate analysis study indicated that posterior lateral frontal cortex contains information about sensory modality, but this study did not identify specific visual-biased and auditory-biased frontal cortical areas (Tamber-Rosenau et al, 2013). …”
Section: Discussionsupporting
confidence: 89%
“…While one recent multivariate analysis indicated that posterior lateral frontal cortex contains information reflecting input sensory modality (Tamber-Rosenau et al, 2013), prior human univariate functional magnetic resonance imaging (fMRI) studies of vision and audition either point to shared multi-sensory structures in lateral frontal cortex (Lewis et al, 2000; Johnson and Zatorre, 2006; Ivanoff et al, 2009; Karabanov et al, 2009; Tark and Curtis, 2009; Tombu et al, 2011; Braga et al, 2013) or report a lateral frontal cortical bias for only one modality (for example, see Crottaz-Herbette et al, 2004; Jantzen et al, 2005; Rämä and Courtney, 2005; Salmi et al, 2007), which could reflect differences in task difficulty rather than sensory modality. Studies in non-human primates have reported distinct areas in lateral frontal cortex that are biased toward audition or vision in anatomical connectivity and/or functional response (for example, see Barbas and Mesulam, 1981; Petrides and Pandya, 1999; Romanski and Goldman-Rakic, 2002; Romanski, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Duncan, 2010; Duncan & Owen, 2000). Tamber-Rosenau et al (2013) reported evidence for modality sensitivity in posterior LFC using a multivariate analysis approach, however their results did not reveal sensory-biases at the level of individual ROIs. In contrast to many past studies, our previous work used individual subject analyses to reveal the fine-grained pattern of modality bias in LFC (Michalka et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…However, consistent with non-human primate studies, two recent human fMRI studies (Michalka et al, 2015; Mayer et al, 2017) and one study combining functional and structural connectivity (Braga et al, 2017) found that distinct regions of LFC exhibit strong biases for vision or audition. Another study also reported sensitivity to sensory modality within LFC (Tamber-Rosenau et al, 2013). …”
Section: Introductionmentioning
confidence: 96%
“…Second, regions of the prefrontal cortex—including anterior cingulate, frontal operculum, and anterior insula—are activated across a very wide variety of cognitive tasks (Duncan, 2010), consistent with central attention that is required for any non-automatic task, and seem to change control settings at task-level, rather than trial-level, intervals (Dosenbach et al, 2008). Third, subsets of the lateral prefrontal cortex and anterior insula are invariant to perceptual modality and to representational format (i.e., location versus shape) (Tamber-Rosenau, Dux, Tombu, Asplund, & Marois, 2013; Tamber-Rosenau, Newton, et al, in revision), consistent with highly abstract processes or representations involved in central attention. These latter results are especially suggestive of the serial nature of central attention because if a representation does not contain sensory information but instead only represents abstract, task-relevant information, one would predict interference or cross-talk between simultaneous representations (Huestegge & Koch, 2009; Navon & Miller, 1987), consistent with the need for serial processing.…”
Section: Central Attention Is Serial Mid-level and Peripheral Attmentioning
confidence: 96%